Impact of Celebrity Endorsement on Customer Behavior in Nepalese Commercial Banks (Nepalese Journal of Management Research, 2021)
This study aims to establish the influence of celebrity endorsement on behavior among customers of Nepalese commercial banks. This study employs a descriptive research design. A self-administered survey questionnaire was used as the main primary data gathering instrument. A total of 300 questionnaires were administered (25 for each of 12 commercial banks). Out of them, 69.67 percent of questionnaires were returned and used. Different statistical tools such as mean and regression analysis were used for the analysis. Cronbach’s alpha was used to analyze the reliability of the data. Descriptive statistics show the celebrity endorsement of Nepalese commercial banks affects customers and these customers have moderately perceived that their behavior is to some extent influenced by celebrity endorsement. However, the regression results indicate that celebrity endorsement has a negative impact on customer behavior in Nepalese commercial banks. Therefore, to create a positive impact of celebrity endorsement, companies need to make strategic decisions with regard to the usage of celebrities in advertising campaigns. The companies should also ideally choose certain celebrities who have a high degree of legitimacy in the minds of the majority of the customers in the country.